Molecular recording of cellular protein kinase activity with chemical labeling - Sun, De-en; Ng, Siu Wang; Zheng, Yu; Xie, Shu; Schwan, Niklas; Breuer, Paula; Hoffmann, Dirk C.; Michel, Julius; Domínguez Azorín, Daniel; Boonekamp, Kim E.; Winkler, Frank; Wick, Wolfgang; et al. (Nature chemical biology, 2025)
Protein kinases control most cellular processes and aberrant kinase activity is involved in numerous diseases. Here we introduce molecular recorders of kinase activities for later analysis to investigate the link between specific kinase activities and cellular phenotypes in heterogeneous cell populations and in vivo. Based on split-HaloTag and a phosphorylation-dependent molecular switch, our recorders become rapidly labeled in the presence of a specific kinase activity and a fluorescent HaloTag substrate. The kinase activity in a given cell controls the degree of fluorescent labeling, whereas the recording window is set by the presence of the fluorescent substrate. We designed specific recorders for four protein kinases, including protein kinase A. We apply our protein kinase A recorder to sort heterogeneous cell populations for subsequent transcriptome analysis, in genome-wide CRISPR screens to discover regulators of PKA activity and to track neuromodulation in freely moving mice.
Gesehen am 22.09.2025